Pengaruh Service Quality (Tangible, Empathy, Reliability, Responsiveness dan Assurance) terhadap Customer Satisfaction: Penelitian pada Hotel Serela Bandung - Yunus Alaan (Jurnal Manajemen Maranatha, 2016)
In the past the service companies lagged behind manufacturing company in the field of the use of marketing as a service company was small, or are business professionals who do not use marketing or face a lot of demand or a little competition, but at the present time services is an important area, where a sector services provide a major contribution in Indonesia. Increase the number of service providers has resulted in increased competition in the services sector, including thehotel services provider, in order to win the competition, service providers need to provide maximum satisfaction to the consumer ,. This study aims to examine and analyze whether quality of service along with the dimensions of quality of servicehas an influence on customer satisfaction. Research conducted on Serela Hotel Bandung by taking a sample of 100 consumers then testing the feasibility of data using SPSS and then do regression testing. The results showed that the effect ofservice quality on customer satisfaction by 35.80%. While the dimensions of the quality of service that has is tangible (30.25%) and reliability (26.41%) on customer satisfaction. So tangible to have the most impact on customer satisfaction.Keywords: Assurance, Customer Satisfaction, Empathy, Reliability, Responsiveness, Service Quality, Tangible